Improved Student Learning OutcomesIIn Learning Theme 4 Clean And Healthy Living At Home With Video Media And Power Points On Google Meet - Prayitno, Wahab (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve student learning outcomes on clean and healthy living materials at home in grade II elementary schools with the Project Based Learning (PjBL) learning model on google meet. The research conducted was a Classroom Action Research (CAR) in two cycles, with each cycle consisting of one meeting. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting is carried out with a knowledge assessment and attitude assessment to determine the development of students. In cycle I students who completed after carrying out the post test were 33%. In cycle II participants students who completed after carrying out the post test were 89%. These results indicate that the Project Based Learning (PjBL) learning model can improve the learning outcomes of students in theme 4 living clean and healthy in Class II homes at SDN 2 Gringgingsari.